PELAKSANAAN PEMBANGUNAN BIDANG KESEHATAN DI KECAMATAN KAYAN SELATAN KABUPATEN MALINAU - Everiady Laing (Magister Administrasi Publik FISIP Universitas Mulawarman, 2020)
This study ains to find out about the implementation of health development in the Southern Kayan District, Malinau District. The type of this research is descriptive and analyzed by using qualitative method, data analysis using interactive model data analysis technique. The results showed that the implementation of health development in Kecamatan Kayan Selatan Malinau District has shown significant progress but has not achieved what is expected and still seems slow. It is seen from the facilities and infrastructure of health has not been adequate and has not reached the standards and the lack of health personnel located in the hinterlands, so that health services to the community has not run optimally.Keywords: Development, Health, Human Resources,